Validation of Malay Version of the COVID-19 Burnout Scale - Ang, Chin Siang; Lee, Kai Wei; Voon, Siok Ping; Ho, Meng Chuan; Tan, Chai Eng; Ching, Siew Mooi *; Ooi, Pei Boon * (Oman Medical Specialty Board, 2023)
Objectives: From early 2020, Malaysia had to implement nationwide lockdowns, quarantines, and other social distancing practices to contain the spread of COVID-19 virus, leading to symptoms of psychosocial burnout among the people. The aim of the present research is to develop and validate a Malay language version of the COVID-19 Burnout Scale (M-COVID-19-BS).